Device and method for evaluating crack resistance of electric arc additive manufacturing material

By designing a crack resistance assessment device for arc additive manufacturing, the image acquisition equipment is used to measure the crack characteristics of the deposited layer and calculate the crack rate of the material, the problem of missing crack resistance assessment in arc additive manufacturing is solved, and reliable assessment and cost-effective evaluation of the crack resistance of the material can be achieved.

CN119555683APending Publication Date: 2025-03-04JIANGSU UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411415813.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In arc additive manufacturing technology, there is a lack of crack resistance assessment devices and methods for materials, which makes it difficult to effectively prevent and control crack defects.

Method used

A device including a general control system, a heat source system, a wire feeding system, a mobile platform, a protective gas system, a substrate and a base plate are designed. The total length of the cracks of the deposited layer and the perimeter of the annular deposited layer are measured by the image acquisition device, and the crack rate of the material is calculated.

Benefits of technology

Reliable assessment of crack resistance of arc additive manufacturing materials is achieved, providing a cost-effective and effective method for evaluating crack resistance of materials, which can comprehensively consider crack resistance under different materials and process conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555683A_ABST
    Figure CN119555683A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of additive manufacturing, in particular to a device and a method for evaluating the crack resistance of an electric arc additive manufacturing material, which can realize related evaluation on the crack resistance in the field of electric arc additive manufacturing. The device is simple in structural design and convenient to operate, the sizes of the base plate and the bottom plate can be flexibly selected according to actual requirements, the crack rate is easy and convenient to calculate, and the crack resistance evaluation result of the electric arc additive manufacturing material is reliable and effective. According to the device, the base plate with the annular groove in the middle is designed, the base plate and the bottom plate are fixed through the bolts, thermal deformation of the base plate caused by heating in the electric arc additive manufacturing process is limited, and meanwhile the restraining degree can be adjusted by adjusting the size parameter proportion of the bottom plate and the base plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a device and method for evaluating the crack resistance of arc additive manufacturing materials. Background Art

[0002] Electric arc additive manufacturing (WAAM) uses welding arc as heat source, melts metal wire through arc heat, and deposits it according to the system preset forming path to obtain a formed part. The significant advantages of WAAM are extremely high material utilization, low cost and efficient and fast near-net forming. However, due to the use of welding arc heat, welding-related defects often appear in WAAM. Cracks are common defects in welded parts, which will directly lead to quality problems of welded products. Under the combined action of stress and other related cracking factors, cracks are very likely to occur. In WAAM, cracks have become a serious defect that affects the quality of formed parts. How to evaluate the crack resistance of materials, that is, to determine the crack sensitivity of materials, plays a very important guiding role in the prevention and control of cracks. At present, there are many measures to prevent and control cracks, including heat treatment and optimization of process parameters, but in the WAAM process, there is a lack of equipment and methods for evaluating the crack resistance of materials, which need to be developed, supplemented and improved. Summary of the invention

[0003] In view of this, the present invention provides a device and method for evaluating the crack resistance of arc additive manufacturing materials, which can realize the relevant evaluation of crack resistance in the field of arc additive manufacturing.

[0004] To achieve the above purpose, the technical solution of the present invention is as follows:

[0005] A device for evaluating the crack resistance of arc additive manufacturing materials comprises: a master control system, a heat source system, a wire feeding system, a mobile platform, a shielding gas system, a substrate, a bottom plate and a fixing part; wherein the master control system is used to control the heat source system, the wire feeding system, the mobile platform and the shielding gas system to deposit the wire on a sample or substrate according to a path preset by a program; receive images acquired by an image acquisition device, analyze the images, and obtain the crack resistance result of the arc additive manufacturing material; the heat source system is used to heat the wire to melt and deposit it; the wire feeding system is used to set the wire feeding speed and transport the wire at the wire feeding speed; the mobile platform is used to move the positions of the substrate, the bottom plate and the fixing part; the shielding gas system is used to protect the heat source system in real time.

[0006] Among them, the substrate has an annular groove in the middle, and the bottom plate is fixed to the substrate, which is used to limit the thermal deformation of the substrate caused by heat during the arc additive manufacturing process, and the constraint degree of the substrate is adjusted by adjusting the size parameter ratio of the bottom plate and the substrate.

[0007] Among them, the master control system measures the total length of cracks on the surface of the sediment layer and the circumference of the annular sediment layer obtained from the test through the images obtained by the image acquisition device, and substitutes the relevant data into the calculation formula of the sediment layer crack rate to calculate the crack rate of the material.

[0008] The calculation formula of the crack rate of the sediment layer is: crack rate = total crack length / circumference of the annular sediment layer.

[0009] The materials of the wire include aluminum and aluminum alloy wire, copper and copper alloy wire, magnesium and magnesium alloy wire, titanium and titanium alloy wire, nickel-based alloy wire, stainless steel wire and steel wire.

[0010] Wherein, the heat source system includes a tungsten inert gas shielded welding heat source, a metal inert gas shielded welding heat source or a cold metal transition heat source.

[0011] The present invention also provides a method for evaluating the crack resistance of arc additive manufacturing materials, which is implemented using the device of the present invention and includes the following steps:

[0012] First, a sample plate made of the same material as the base plate is selected for arc additive manufacturing trial deposition. By depositing a layer, the width of the current deposition layer of the metal wire is determined;

[0013] After cooling, the width of the test deposit layer is measured;

[0014] The base plate is machined to form a circular groove in the middle, through holes are opened at the surrounding positions, and threaded holes are opened at positions corresponding to the base plate on the bottom plate;

[0015] Use alcohol solution to clean the bottom plate and base plate, and fix the two together;

[0016] The metal wire is deposited at the groove according to a circular path pre-set by the program;

[0017] Calculate the crack rate of the annular sediment layer;

[0018] The crack resistance of the metal material can be judged by comparing the crack rates obtained.

[0019] Among them, a layer is deposited along a straight line, and the length of the deposited layer is 0.5-0.8 times the length of the sample.

[0020] Among them, the widths of 3 to 5 positions of the test deposition layer are selected for measurement, and the average value of the widths is calculated.

[0021] Beneficial effects:

[0022] 1. The device of the present invention has a simple structural design and is easy to operate. The sizes of the substrate and the bottom plate can be flexibly selected according to actual needs. The calculation of the crack rate is simple, and the crack resistance evaluation result of the arc additive manufacturing material is reliable and effective.

[0023] 2. A substrate with an annular groove in the middle is designed in the device of the present invention, and the substrate and the bottom plate are fixed by bolts to limit the thermal deformation of the substrate caused by heat during the arc additive manufacturing process. At the same time, the constraint degree can be adjusted by adjusting the ratio of the dimensional parameters of the bottom plate and the substrate. Specifically, the constraint degree can be adjusted by changing the ratio of the groove depth to the substrate thickness.

[0024] 3. The method of the present invention is implemented based on the device of the present invention, and uses the circumference of the deposited layer as the denominator, providing a standardized benchmark for crack rate evaluation. At the same time, the formula does not distinguish between the type and size of cracks, and can comprehensively consider the comparison of crack resistance of materials under different materials and different process conditions.

[0025] 4. In the method of the present invention, by measuring the crack lengths at multiple locations, random errors can also be reduced, and the accuracy and reliability of crack rate assessment can be improved. Compared with crack assessment methods that require complex equipment and high costs, the present invention provides an economical and effective means of assessing material crack resistance.

[0026] 5. In the method of the present invention, when different metal wires are selected for arc additive manufacturing, the crack resistance of arc additive manufacturing of different metal wires is evaluated by measuring the crack rates of deposited layers of different wires.

[0027] 6. In the method of the present invention, for the annular groove, the constraint on the deposited layer during the arc additive manufacturing process can be adjusted by adjusting the ratio of the groove depth to the substrate thickness. When the substrate thickness remains unchanged, the deeper the groove depth, the greater the constraint. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the device for evaluating the crack resistance of arc additive manufacturing materials according to the present invention, wherein A is the master control system, B is the heat source system, C is the wire feeding system, D is the mobile platform, E is the fixing part of the substrate and the bottom plate, and F is the shielding gas system.

[0029] Figure 2 This is a fixed three-dimensional schematic diagram of the substrate and the bottom plate in the device for evaluating the crack resistance of arc additive manufacturing materials of the present invention; wherein 1 is the bottom plate, 2 is the substrate, and 3 is the annular groove.

[0030] Figure 3 This is a schematic top view of the fixing of the substrate and the bottom plate in the device for evaluating the crack resistance of arc additive manufacturing materials according to the present invention. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0032] The present invention provides a device for evaluating the crack resistance of arc additive manufacturing materials. Figure 1 As shown, it includes a general control system, an image acquisition device, a heat source system, a wire feeding system, a moving platform, a protective gas system, a substrate, a bottom plate and fixing parts.

[0033] The master control system is used to control the heat source system, wire feeding system, mobile platform and shielding gas system, and deposit the wire on the sample or substrate according to the path pre-set by the program; receive the image acquired by the image acquisition device, and analyze the image to obtain the crack resistance result of the arc additive manufacturing material. Specifically, the master control system uses the image acquired by the image acquisition device to analyze the total crack length (L c ) and the circumference of the annular sediment layer (C d ) is measured and the relevant data is substituted into the calculation formula of the crack rate of the sedimentary layer: Crack rate (R c ) = total crack length (L c ) / circumference of annular sediment layer (C d ), and calculate the crack rates of the three groups of stainless steel materials.

[0034] The heat source system is used to heat the wire, melt it and deposit it; the wire feeding system is used to set the wire feeding speed and transport the wire at the wire feeding speed; the mobile platform is used to move the position of the substrate, bottom plate and fixings; the protective gas system is used to provide real-time protection for the heat source system.

[0035] In the device of the present invention, the material of the wire can be selected from aluminum and aluminum alloy wire, copper and copper alloy wire, magnesium and magnesium alloy wire, titanium and titanium alloy wire, nickel-based alloy wire, stainless steel wire and high-strength steel wire, etc.; the heat source system can be selected from tungsten inert gas shielded welding (TIG) heat source, melt inert gas shielded welding (MIG) heat source or cold metal transfer (CMT) heat source, etc., and the relevant test parameters are specifically set according to the selected heat source type.

[0036] In the calculation formula for the crack rate of the deposited layer, the circumference of the deposited layer is used as the denominator, which provides a standardized benchmark for crack rate assessment. At the same time, the formula does not distinguish between the type and size of cracks, and can comprehensively consider the crack resistance comparison of different materials and materials under different process conditions. By measuring the crack lengths at multiple locations, random errors can also be reduced, and the accuracy and reliability of crack rate assessment can be improved. Compared with crack assessment methods that require complex equipment and high costs, this formula provides a cost-effective means of assessing material crack resistance. Different metal wires are selected for arc additive manufacturing, and the crack rates of different wire deposits are measured to evaluate the crack resistance of arc additive manufacturing of different metal wires.

[0037] When the device of the present invention is evaluated, the substrate is machined, a circular groove is machined in the middle, through holes are opened at the surrounding positions, and threaded holes are opened at the positions corresponding to the substrate on the bottom plate. The through holes of the substrate and the threaded holes of the bottom plate can be set in specific sizes according to actual needs to ensure that the two are fixedly connected. Among them, the substrate with an annular groove in the middle is fixed to the bottom plate by bolts, which limits the thermal deformation of the substrate caused by heat during the arc additive manufacturing process, and the constraint can be adjusted by adjusting the ratio of the size parameters of the bottom plate and the substrate. For the annular groove, the constraint on the deposited layer during the arc additive manufacturing process can be adjusted by adjusting the ratio of the depth of the groove to the thickness of the substrate. When the thickness of the substrate remains unchanged, the deeper the groove depth, the greater the constraint. During the deposition process, the solidification transition of the deposited layer from liquid to solid will produce solidification shrinkage, and the rapid cooling of the deposited layer will produce cooling shrinkage, but because the deposited layer is connected to the inner and outer side walls of the groove, the free shrinkage of the deposited layer is hindered, thereby generating tensile stress on the deposited layer, resulting in cracking. Under this setting, cracks tend to appear on the surface of the sediment layer. Compared with other crack parameters (such as crack depth, shape, etc.), the measurement of the total crack length and the circumference of the sediment layer is relatively simple, convenient for operation and field application.

[0038] Furthermore, the device of the present invention has a simple structural design and is easy to operate. The size of the substrate and the bottom plate can be flexibly selected according to actual needs, and the degree of restraint can be adjusted by changing the ratio of the groove depth to the substrate thickness. The calculation of the crack rate is simple, and the crack resistance evaluation result of the arc additive manufacturing material is reliable and effective. The device of the present invention has a wide range of applications and has important guiding significance for efficient and high-quality arc additive manufacturing.

[0039] The present invention also provides a method for evaluating the crack resistance of arc additive manufacturing materials, comprising the following steps:

[0040] First, a sample plate made of the same material as the base plate is selected for arc additive manufacturing test deposition. By depositing a layer, the width of the current deposited layer of the metal wire is determined; after cooling, the width of the test deposited layer is measured;

[0041] The substrate is machined to form a circular groove in the middle and through holes are opened around it; threaded holes are opened on the bottom plate at positions corresponding to the substrate; the bottom plate and the substrate are cleaned with an alcohol solution and fixed with bolts; a welding gun is used to deposit the metal wire at the groove according to the circular path pre-set by the program;

[0042] The crack rate of the annular sediment layer is calculated by measuring the total length L of the sediment layer cracks. c and the perimeter of the sediment layer C dThe calculated results are compared with the obtained crack rates to determine the crack resistance of the metal material.

[0043] Among them, the size width of the sample (W Y ) can be set to 20-30mm, length (L Y ) can be set to 100-150mm, thickness (δ Y ) can be set to at least 1 mm. The specific size of the sample can be selected according to actual needs.

[0044] In this embodiment, a layer is deposited along a straight line, and the length of the deposited layer is 0.5-0.8 times the length of the sample.

[0045] The width of 3 to 5 locations of the test deposition layer can be measured and the average width (W P ).

[0046] In this embodiment, the width of the bottom plate (W d ) and length (L d ) can be set to 75-200mm, the width of the substrate (W b ) and length (L b ) can be set to 50-150mm, the thickness of the bottom plate (δ d ) and the thickness of the substrate (δ b ) is not less than 2mm; the inner diameter of the annular groove (d a ) is the substrate width (W b ) is 0.3-0.7 times, the depth of the groove (D a ) is 0.2-0.8 times the substrate thickness (δ), and the width (W a ) should be set based on the average width of the test deposition layer (W P ), the width of the groove (W a ) and the average width value (W P )equal.

[0047] The crack rate of the deposited layer can be calculated using the following formula: Crack rate (Rc) = total crack length (Lc) / circumference of the annular deposited layer (Cd). The length is measured by an image acquisition device connected to the welding gun, and the crack rate is obtained by automatic calculation by the master control system. The way to evaluate the crack resistance of arc additive manufacturing materials is to sort the crack rates measured by different wires under the same conditions. The higher the crack rate, the worse the crack resistance of the material; the lower the crack rate, the better the crack resistance of the material. If Rc1>Rc2, the crack resistance of the arc additive manufacturing material with a crack rate of Rc2 is better than that of the arc additive manufacturing material with a crack rate of Rc2.

[0048] Embodiment 1 of the method of the present invention: A tungsten inert gas shielded welding (TIG) heat source is selected, 304 stainless steel, 310 stainless steel and 316 stainless steel are selected as wire materials, and 1060 pure aluminum plates are used for the sample, substrate and bottom plate, and the crack resistance of different materials manufactured by arc additive manufacturing is evaluated:

[0049] Plate preparation: 1060 pure aluminum plate was cut by wire cutting to obtain 3 samples, the length (L Y ) is 100mm, width (W Y ) is 20 mm, thickness (δ Y ) is 2 mm; 3 substrates are obtained, and their length (L b ) is 50mm, width (W b ) is 50 mm, thickness (δ b ) is 5mm; 3 bottom plates are obtained, and their length (L d ) is 75mm, width (W d ) is 75mm, thickness (δ d ) is 7mm.

[0050] Sample cleaning: Before arc additive manufacturing trial deposition, three samples were cleaned with alcohol to remove water and oil stains.

[0051] Sample deposition test: The test parameters are set as 100A current, 20V voltage, 300cm / min wire feeding speed, and 30cm / min deposition speed. Use different stainless steel wires to deposit a layer along a straight line on the surface of three samples, with a deposition length of 50mm.

[0052] Determine the groove width (W a ): After the sample is cooled, take the average width measurement of the starting position, middle position and end position of each sample (W p ), and the average width of 304 stainless steel wire (W p1 ) is 8mm, the average width of 310 stainless steel wire (W p2 ) is 8mm, the average width of 316 stainless steel (W p3 ) is 7mm. The width of the groove (W a ) is equal to the average width of the deposited layer of the three wire materials.

[0053] Machining: The inner diameter (d a ) is 20mm, the depth (Da) is 2mm, the groove width (W a1 , W a2 , W a3) are 8mm, 8mm and 7mm respectively. Through holes with a diameter of 3mm are opened around the three substrates, and M3 threaded holes are opened at the positions corresponding to the through holes of the three bottom plates and substrates. The size design of the corresponding positions can refer to the schematic diagram Figure 3 .

[0054] Plate cleaning: Before arc additive manufacturing deposition, the three substrates and the base plate were cleaned with alcohol to remove water and oil stains.

[0055] Restraint application: Use M3 bolts to fix 3 base plates and 3 bottom plates to obtain 3 sets of test devices, which can be referred to in the schematic diagram. Figure 2 .

[0056] Test conduct: The arc additive manufacturing process was used, and the test parameters of current value, voltage value, wire feeding speed and deposition speed were the same as those of the trial deposition test. The starting position was set in the equipment program, and a circular path for deposition along the groove was planned. The three types of stainless steel wire were deposited at the groove on the corresponding device according to the circular path pre-set by the program using a welding gun, and two layers were deposited. Under the action of the TIG heat source, the stainless steel wire melted and deposited on the surface of the groove. During the deposition process, the deposited layer connected with the inner and outer walls of the groove, causing cracks to form and expand along the circular path. After the first layer was deposited, the second layer was deposited along the same path.

[0057] Crack rate calculation: After the three sets of devices are cooled, the total length of cracks on the surface of the deposited layer obtained from the three sets of tests (L c ) and calculate the circumference of the annular sediment layer (C d ), substitute the relevant data into the calculation formula of the crack rate of the sedimentary layer: Crack rate (R c ) = total crack length (L c ) / circumference of annular sediment layer (C d ), the crack rate of the three groups of stainless steel materials was calculated. The crack rate of the deposited layer of 304 stainless steel wire (R c1 ) is 30.7%, and the crack rate of the deposited layer of 310 stainless steel wire (R c2 ) is 63.5%, and the crack rate of the deposited layer of 316 stainless steel wire (R c3 ) is 44.8%.

[0058] Crack resistance evaluation: The crack rates of the three stainless steel wires measured under the same conditions were ranked to determine their crack resistance. The results showed that 304 stainless steel wire > 316 stainless steel wire > 310 stainless steel wire, thus achieving the evaluation of crack resistance of arc additive manufacturing materials.

[0059] Example 2 of the method of the present invention: A cold metal transition (CMT) heat source is selected, 2219 aluminum alloy, 6061 aluminum alloy and 7075 aluminum alloy are selected as wire materials, and 1060 pure aluminum plates are used for the sample, substrate and bottom plate, and the crack resistance of different materials manufactured by arc additive manufacturing is evaluated:

[0060] Plate preparation: 1060 pure aluminum plate was cut by wire cutting to obtain 3 samples, the length (L Y ) is 150mm, width (W Y ) is 30 mm, thickness (δ Y ) is 3 mm; 3 substrates are obtained, and their length (L b ) is 150mm, width (W b ) is 150mm, thickness (δ b ) is 6mm; 3 bottom plates are obtained, and their length (L d ) is 200mm, width (W d ) is 200mm, thickness (δ d ) is 8mm.

[0061] Sample cleaning: Before conducting arc accumulation manufacturing trial deposition, clean the three samples with alcohol to remove water and oil stains.

[0062] Sample deposition test: The test parameters are set to 90A current, 15V voltage, 280cm / min wire feeding speed, and 25cm / min deposition speed. Different aluminum alloy wires are used to deposit a layer along a straight line on the surface of three samples, and the deposition length is 100mm.

[0063] Determine the groove width (W a ): After the sample is cooled, take the average width measurement of the starting position, middle position and end position of each sample (W p ), and the average width (W p1 ) is 6mm, the average width of 6061 aluminum alloy wire (W p2 ) is 5 mm, the average width of 7075 aluminum alloy wire (W p3 ) is 5mm. The width of the groove (W a ) is equal to the average width of the deposited layer of the three wire materials.

[0064] Machining: The inner diameter (d a ) is 90mm, depth (D a ) is a 3mm circular groove, the groove width (W a1 , W a2 , W a3) are 6mm, 5mm and 5mm respectively. Through holes with a diameter of 6mm are opened around the three substrates, and M6 threaded holes are opened at the positions corresponding to the through holes of the three bottom plates and substrates. The size design of the corresponding positions can refer to the schematic diagram Figure 3 .

[0065] Plate cleaning: Before arc deposition, clean the three substrates and the base plate with alcohol to remove water and oil stains.

[0066] Restraint application: Use M6 bolts to fix 3 base plates and 3 bottom plates to obtain 3 sets of test devices, which can be referred to in the schematic diagram. Figure 2 .

[0067] Test conduct: Arc additive manufacturing process was used, and the test parameters of current value, voltage value, wire feeding speed and deposition speed were the same as those of the trial deposition test. The starting position was set in the equipment program, and a circular path for deposition along the groove was planned. The three aluminum alloy wires were deposited at the groove in the corresponding device according to the circular path pre-set by the program using a welding gun, and two layers were deposited. Under the action of the CMT heat source, the aluminum alloy wire melted and deposited on the surface of the groove. During the deposition process, the deposited layer connected with the inner and outer side walls of the groove, causing cracks to be generated and extended along the circular path. After the first layer was deposited, the second layer was deposited along the same path.

[0068] Crack rate calculation: After the three sets of devices are cooled, the total length of cracks on the surface of the deposited layer obtained from the three sets of tests (L c ) and calculate the circumference of the annular sediment layer (C d ), substitute the relevant data into the calculation formula of the crack rate of the sedimentary layer: Crack rate (R c ) = total crack length (L c ) / circumference of annular sediment layer (C d ), the crack rates of the three groups of aluminum alloy materials were calculated. The crack rate of the deposited layer of 2219 aluminum alloy wire (R c1 ) is 20.5%, and the crack rate of the deposited layer of 6061 aluminum alloy wire (R c2 ) is 52.3%, and the crack rate of the deposited layer of 7075 aluminum alloy wire (R c3 ) is 32.6%.

[0069] Crack resistance evaluation: The crack rates of the three aluminum alloy wires measured under the same conditions were ranked to determine the crack resistance of the three aluminum alloy wires. The results showed that 2219 aluminum alloy wires > 7075 aluminum alloy wires > 6061 aluminum alloy wires, thus achieving the evaluation of the crack resistance of arc additive manufacturing materials.

[0070] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A device for evaluating the crack resistance of arc additive manufacturing materials, characterized in that: include: A general control system, a heat source system, a wire feeding system, a mobile platform, a shielding gas system, a substrate, a bottom plate and fixings; wherein the general control system is used to control the heat source system, the wire feeding system, the mobile platform and the shielding gas system, and deposit the wire on the sample or substrate according to the path pre-set by the program; receive the image acquired by the image acquisition device, and analyze the image to obtain the crack resistance result of the arc additive manufacturing material; the heat source system is used to heat the wire to melt and deposit it; the wire feeding system is used to set the wire feeding speed and transport the wire at the wire feeding speed; the mobile platform is used to move the position of the substrate, the bottom plate and the fixings; the shielding gas system is used to protect the heat source system in real time.

2. The device according to claim 1, characterized in that The substrate has an annular groove in the middle, and the bottom plate is fixed to the substrate to limit the thermal deformation of the substrate caused by heat during the arc additive manufacturing process. The constraint degree of the substrate is adjusted by adjusting the size parameter ratio of the bottom plate and the substrate.

3. The device according to claim 1, characterized in that The master control system measures the total length of cracks on the surface of the sediment layer and the circumference of the annular sediment layer obtained through the images acquired by the image acquisition device, and substitutes the relevant data into the calculation formula of the sediment layer crack rate to calculate the crack rate of the material.

4. The device according to claim 3, characterized in that The calculation formula of the crack rate of the sediment layer is: crack rate=total crack length / circumference of the annular sediment layer.

5. The device according to any one of claims 1 to 4, characterized in that: The materials of the wire include aluminum and aluminum alloy wire, copper and copper alloy wire, magnesium and magnesium alloy wire, titanium and titanium alloy wire, nickel-based alloy wire, stainless steel wire and steel wire.

6. The device according to any one of claims 1 to 4, characterized in that: The heat source system comprises a tungsten inert gas shielded welding heat source, a metal inert gas shielded welding heat source or a cold metal transition heat source.

7. A method for evaluating the crack resistance of arc additive manufacturing materials, characterized in that: The method is implemented by using the device according to any one of claims 1 to 6, comprising the following steps: First, a sample plate made of the same material as the base plate is selected for arc additive manufacturing trial deposition. By depositing a layer, the width of the current deposition layer of the metal wire is determined; After cooling, the width of the test deposit layer is measured; The base plate is machined to form a circular groove in the middle, through holes are opened at the surrounding positions, and threaded holes are opened at positions corresponding to the base plate on the bottom plate; Use alcohol solution to clean the bottom plate and base plate, and fix the two together; The metal wire is deposited at the groove according to a circular path pre-set by the program; Calculate the crack rate of the annular sediment layer; The crack resistance of the metal material can be judged by comparing the crack rates obtained.

8. The method according to claim 7, characterized in that Try to deposit a layer along a straight line, and the length of the deposited layer is 0.5-0.8 times the length of the sample.

9. The method according to claim 7 or 8, characterized in that The widths of 3 to 5 locations of the test deposition layer were selected for measurement, and the average value of the widths was calculated.